2022
DOI: 10.2196/39012
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Publications on Nursing for COVID-19 in Patients With Cancer: Scoping Review

Abstract: Background The needs of patients with cancer must be met, especially in times of crisis. The advent of the pandemic triggered a series of strategic actions by the nursing team to preserve the health of patients and professionals—hence the importance of studies on nursing care actions provided to patients with cancer during the COVID-19 pandemic. It is known that these patients are susceptible to severe COVID-19. However, no previous review has summarized the findings of scientific studies on nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…(2022) con rmed that health professionals have dedicated themselves to gardening, cooking, dog walks, and yoga classes through video to counteract di culties and reduce stress [33]. Another aspect that emerged was related to the use of video calls with friends, relatives, and caregivers: some authors have reported that the use of such technology as Face Time or Zoom to feel the absence of hospital visits and social gatherings less has contributed to reducing the isolation and distance between patients, friends, and family [33,37,38,42]. An aspect that did not emerge from our study, but has been reported in the literature [33,37,42] concerns the increased use of telemedicine to help patients who could not access hospital care because of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…(2022) con rmed that health professionals have dedicated themselves to gardening, cooking, dog walks, and yoga classes through video to counteract di culties and reduce stress [33]. Another aspect that emerged was related to the use of video calls with friends, relatives, and caregivers: some authors have reported that the use of such technology as Face Time or Zoom to feel the absence of hospital visits and social gatherings less has contributed to reducing the isolation and distance between patients, friends, and family [33,37,38,42]. An aspect that did not emerge from our study, but has been reported in the literature [33,37,42] concerns the increased use of telemedicine to help patients who could not access hospital care because of COVID-19.…”
Section: Discussionmentioning
confidence: 99%